Racial origin and primary renal diagnosis in 771 patients with end-stage renal disease. - Pazianas, M; Eastwood, J; MacRae, K; Phillips, M (1991)
A total of 771 individuals with end-stage renal disease treated at one centre from 1964 to 1990 were studied. Data on racial origin, gender, age, and primary renal diagnosis were analysed. The male: female ratio (468:303) and proportions of individuals in different diagnostic groups (renal diagnosis based on European Dialysis and Transplant Association (EDTA) groups) were similar to EDTA data for the UK as a whole. Racial distribution was Caucasian 79.0%, Indian subcontinent (Is-c) 12.7%, Caribbean, 5.6%, African 1.6% and other Asian 1.2%. In Britain individuals from the Is-c constitute 2.2% of the general population and those from the Caribbean 1.0%. We found differences in the distribution of primary renal disease among patients from different racial groups. Adult polycystic kidney disease was almost entirely confined to Caucasians (75 to 79 patients). Diabetic nephropathy was relatively more common in individuals (especially males) from the Is-c. Hypertensive renal disease was relatively more common in those of Caribbean descent and in Africans, whilst 'Unknown diagnosis' was most common in patients from the Is-c.